A self-report measure of diabetes-specific anxiety symptoms for adolescents. Issue 2 (3rd April 2023) - Rechenberg, Kaitlyn; Szalacha, Laura; Bugajski, Andrew
ABSTRACT: Adolescents with Type 1 diabetes experience anxiety symptoms specifically related to the self-management of diabetes. The purpose of this study is to describe the initial psychometric testing of the Anxiety Symptoms in Diabetes Scale in Adolescents (ASDS-A), a 14-item instrument designed to measure diabetes-specific anxiety. Following an in-depth qualitative study, items were identified and reviewed by experts, and remaining items were tested in 146 adolescents. A PCA indicated a single dimension (Eigenvalue, 6.106) with a Cronbach's α of .896, leaving a 14-item measure. There is strong evidence that the ASDS-A is a developing reliable and valid measure of diabetes-specific anxiety.